Spatial and temporal aspects of genetic variation in sea urchin, tripneustes gratilla populations in Western Luzon, Philippines - Casilagan, Inggat Laya N. (Marine Science Institute, College of Science, University of the Philippines Diliman, 2011)
Tripneustes gratilla is known for its ecological and economic importance across the Indo-Pacific. It is the most important commercial sea urchin species in the Philippines. In northwestern Luzon, artisanal fisheries supported by T. gratilla populations persist but to ensure the sustainability of this invertebrate resource, effective management is necessary. On this premise, T. gratilla populations along the coast of western Luzon were re-assessed using genetic markers to obtain relevant information on population delineation and connectivity.